Development of a Web-Based Interactive E-Module Application as an Innovative Biology Learning Media - Hanina, Putri Urfi; Nurcahyanto, Guntur (Universitas Muhammadiyah Surakarta, 2024)
Today's rapid technological advances require teachers and students to be active and skilled in using technology. Teachers need more skills in creating educational materials, especially on the human excretory system, which needs visual aids for easier student comprehension. This research aims to determine the feasibility of interactive e-module learning media on human excretory system material and analyze student responses to the media developed. This research uses the Research & Development method by utilizing the 4D development design introduced by Thiagarajan, which consists of four stages: define, design, develop, and disseminate. The research subjects consisted of 25 class VIII students of SMP Muhammadiyah PK Kottabarat Surakarta. The research instrument used a questionnaire to assess the suitability of the E-module according to media experts and material experts, as well as a student response questionnaire to the E-modul, which was tested using a usability test. The research results show that. 1). According to media experts, the feasibility of the e-module is in the feasible category, with a score of 83.125%. 2). According to material experts, is in the very feasible category with a score of 81.9% and 3). The student's response received a score of 80.3 in the very good category. So the Interactive Science E-Module learning media is suitable for use as material for human excretory systems in class VIII of junior high school.